Teaching university lecturers how to teach subject : specific writing - Manderstedt, Lena; Palo, Annbritt (Luleå tekniska universitet, Pedagogik, språk och Ämnesdidaktik, 2015)
Teaching university lecturers how to teach subject-specific writingLena Manderstedt, Annbritt PaloStandards of student literacy are falling, due to an increased number of students described as non-traditional entrants not knowing how to write (Lea & Street, 1998). Extensive research into academic literacy practices has been carried out, including genre pedagogy (Martin, 2009), the effectiveness of feedback (Hattie & Timperley, 2007) and the role of assessment as a key to develop and improve student learning. Academic literacies models, including digital literacies, have been adopted and used in course design and in the design of writing instructions (Lea & Jones, 2011; Wingate, 2012). However, students still lack academic writing skills.Although Luleå University of Technology (LTU) set up a language lab in 2006, and the lab was appreciated by students, it is not the most efficient way to teach academic writing. Therefore, a pedagogical project, aiming to help students develop their academic writing proficiency, and to help subject teachers learn how to scaffold subject-specific academic writing started in 2014. The first part of the project, directed at students, took place in the autumn of 2014. The results pinpoint the importance of contextualizing and scaffolding subject-specific writing through deliberative discussions. Students also emphasised the need for subject-oriented writing in order to develop academic literacy. The second part of the project involved the design of a University Pedagogy course, based on research and on the outcome of the first part. The aim of the course is to teach university lecturers how to teach subject-oriented writing, by systematic training in contextualizing subject-oriented writing, designing instructions, and dialogues focussing texts within their respective disciplines. The course is to be given in 2015 or 2016.The aim of this roundtable-presentation is to get valuable feedback on the planned course design. We wish to discuss examples of teaching ...